Robert E. Howard : a Collector's Descriptive Bibliography of American and British Hardcover, Paperback, Magazine, Special and Amateur Editions, with a Biography. - Nielsen, Leon (McFarland & Company, Inc., Publishers, 2010)
Robert E. Howard published primarily in pulp magazines, creating memorable characters like Conan of Cimmeria. After his suicide at the age of 30, pulps continued publishing Howard material posthumously. His first hardcover book appeared in 1937, a year after his death. That book, A Gent from Bear Creek, is the holy grail for Howard collectors--only 12 original copies are known to exist. This invaluable resource for Howard collectors has information for every known published work. Initial chapters provide a biography, discuss Howard's literary legacy, and give basic tips about book collecting a.